2008
DOI: 10.2174/138161208784746833
|View full text |Cite
|
Sign up to set email alerts
|

HCV Screening to Enable Early Treatment of Hepatitis C: A athematical Model to Analyse Costs and Outcomes in Two Populations

Abstract: Early treatment of acute hepatitis C virus (HCV) infections reflects a new clinical paradigm and a significant option to reduce the socioeconomic burden of HCV. Therefore, this approach seems suitable as a new strategy to face HCV and prevent end stage liver diseases and premature deaths due to progressed chronic HCV-infections. The main limitation of this approach is that the majority of acute infections show an asymptomatic course and do thus not present to the health-care settings. Screening for HCV has alr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…To our knowledge, no previous study has considered the cost effectiveness of routine screening for acute HIV infection in IDUs. Our results differ from the one study that considered the cost effectiveness of screening IDUs for acute/early HCV infection; that study found antibody screening every 6 months and initiation of treatment to be highly cost effective and potentially cost-saving [122]. However, that study assumed that 100% of identified cases among IDUs would be eligible for PEG-IFN+RBV treatment and did not include the possibility of re-infection, which is known to occur [123].…”
Section: Discussioncontrasting
confidence: 95%
“…To our knowledge, no previous study has considered the cost effectiveness of routine screening for acute HIV infection in IDUs. Our results differ from the one study that considered the cost effectiveness of screening IDUs for acute/early HCV infection; that study found antibody screening every 6 months and initiation of treatment to be highly cost effective and potentially cost-saving [122]. However, that study assumed that 100% of identified cases among IDUs would be eligible for PEG-IFN+RBV treatment and did not include the possibility of re-infection, which is known to occur [123].…”
Section: Discussioncontrasting
confidence: 95%
“…However, no costs for the screening programme were taken into account and compliance was set at an unrealistic 100%. Five economic analyses of HCV screening of other population subgroups were found [48,50,63,65,66,74]. Both studies that considered screening programmes targeting several population subgroups concluded that the specific programmes considered were potentially cost-effective [50,66].…”
Section: Resultsmentioning
confidence: 99%
“…Josset et al reported estimated costs per positive test result for 6 screening scenarios, which varied regarding population subgroups targeted [63]. Analyses of HCV screening of people transfused before 1991 in France and of people with a history of surgery in Italy both concluded this was not cost-effective [48,65]. …”
Section: Resultsmentioning
confidence: 99%
“…Considerable work has been undertaken to forecast the epidemiology of hepatitis C and numerous authors have developed Markov models to estimate the disease burden (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, these models have limitations resulting from the assumption that the studied cohorts remain homogeneous and traverse through different states at a fixed rate over time when, in reality, populations are very heterogeneous (17).…”
mentioning
confidence: 99%